Biofuel regulations in the USA and the EU - Nagy, Orsolya (Acta Agraria Debreceniensis, 2014)
Climate change, the increasing dependency on crude oil and other fossile fuels, the expanding import and the increasing energy costs make the world’s societies and its economies vulnerable. The development of effective renewable energy resources has been a priority for the US since the first oil embargo. While there was only little progress for around two decades, biofuel use and production has been showing a rapidly increasing tendency since the mid 90’s. The EU’s objective of renewable energy resources is one of the main priorities of the Europe 2020 strategy. The European Union aims to increase the share of energy produced from renewable resources in the whole energy supply and by 10% in the transport-related energy supply by 20% until 2020. The renewable energy sector is the only one which is able to reduce GHG emission and pollution while utilising local energy resources and stimulating cutting edge industrial sectors; therefore, it is indispensable to develop a proper framework and regulation for supporting renewable energies.